2008
DOI: 10.1016/j.semcdb.2007.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Corneal crystallins and the development of cellular transparency

Abstract: Past studies have established that the cornea like the lens abundantly expresses a few water-soluble enzyme/proteins in a taxon specific fashion. Based on these similarities it has been proposed that the lens and the cornea form a structural unit the 'refracton' that has co-evolved through gene sharing to maximize light transmission and refraction to the retina. Thus far, the analogy between corneal crystallins and lens crystallins has been limited to similarities in the abundant expression, with few reports c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
129
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 67 publications
3
129
0
4
Order By: Relevance
“…However, our results showed that the size of the keratocytes maintaining transparency in the birds and rat were smaller than that in the rabbit. Corneal crystallins such as ALDH, which have been shown to protect against UV and oxidative stress induced apoptosis, are expressed abundantly in keratocytes [10,20,23,26,31]. The protein expression of crystallins in keratocytes of the birds and rat may be more abundant than that in the rabbit and not be dependent on the size of the keratocyte.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results showed that the size of the keratocytes maintaining transparency in the birds and rat were smaller than that in the rabbit. Corneal crystallins such as ALDH, which have been shown to protect against UV and oxidative stress induced apoptosis, are expressed abundantly in keratocytes [10,20,23,26,31]. The protein expression of crystallins in keratocytes of the birds and rat may be more abundant than that in the rabbit and not be dependent on the size of the keratocyte.…”
Section: Discussionmentioning
confidence: 99%
“…One of the roles of the keratocyte is the maintenance of normal corneal transparency [33]. Keratocytes contain corneal crystallins, such as aldehyde dehydrogenase (ALDH), which are highly expressed proteins that contribute to the transparent nature of the cornea [20][21][22]33]. Keratocytes are normally quiescent, but they can readily respond and transition into repair phenotypes following injury [33].…”
mentioning
confidence: 99%
“…Recent research has identified the importance of the intracellular protein expression of these keratocytes in maintaining corneal transparency. [3][4][5] The keratocytes in the quiescent phenotype express two characteristic proteins: transketolase (TKT) and aldehyde dehydrogenase class 1A1 (ALDH1A1). 3 A decrease in expression of TKT and ALDH1A1 expression in keratocytes leads to a marked decrease in corneal transparency and increased light scattering from keratocytes.…”
mentioning
confidence: 99%
“…3 A decrease in expression of TKT and ALDH1A1 expression in keratocytes leads to a marked decrease in corneal transparency and increased light scattering from keratocytes. [3][4][5] In response to corneal wounding, the keratocytes differentiate into repair fibroblasts and eventually myofibroblasts. The myofibroblast phenotype is characterized by intracellular expression of the contractile protein a-smooth muscle actin (a-SMA).…”
mentioning
confidence: 99%
See 1 more Smart Citation